Journalism and public relations: An interconnection in academic research - Supriadi, Dandi; Hafiar, Hanny; Safi, Abdul Manan; Amin, Kholidil (Universitas Padjadjaran, 2023)
Background: Journalism and public relations are two fields that collaborate and compete with each other. Several studies have confirmed this dualism, where both terminologies are interrelated in the same scientific publication. Purpose: This study is aimed to find the interconnection between the two fields in several studies published in international journals. Method: This inquiry applies the bibliometrics method with data sources from the Web of Science and uses VosViewer as an analysis and mapping tool. Results: Results show that the number of keywords containing “public relations” counts more than “journalism.” This study reveals six clusters of keyword mapping that form specific themes: crisis communication management, ethics, professional education, public relations practitioners- journalist relationships, media relations, and publicity scope, news media management, and public relations and the media. Comparing the most cited references from the field of public relations and journalism shows the number 2:2 or equal. There are six most cited authors, four from the USA and two from Australia. Conclusions: The issue of public relations was found more than journalism because most articles are written by experts, especially Americans, and Australians, who have worked in the field of public relations, although some also had early careers in journalism. However, journalism studies were still considered as references for most articles. Implications: The work of western researchers is still at the forefront of the development of public relations science and journalism studies, which becomes a challenge for researchers from developing countries to develop studies more at the international level.